Perspectives in business informatics research : 16th International Conference, BIR 2017, Copenhagen, Denmark, August 28-30, 2017, Proceedings /: 16th International Conference, BIR 2017, Copenhagen, Denmark, August 28-30, 2017, Proceedings. (2017) - Unknown
No abstract available